A miniaturized angularly stable dual‐band FSS based on convoluted structure and complementary coupling. Issue 6 (25th February 2022) - He, Zhangjian; Shao, Yu; Zhang, Changhong; Wang, Ping; Zhang, Jie
Abstract: A miniaturized dual‐band frequency selective surface (FSS) with high angular stability is proposed. The unit cells of the proposed FSS have a convoluted pattern and hexagonal contour, which are arranged into array compactly. The FSS is implemented on single substrate with two metallic layers which has a low profile. The top and bottom patterns are complementary which generate two passbands separated by a transmission zero. A high out‐of‐band suppression is obtained, and the two bands can be tuned simply and flexibly. The FSS is highly stable with respect to different incident angles and polarizations due to the rotationally symmetric structure. An equivalent circuit model is developed, and a prototype working at 2.15 GHz and 3.8 GHz is fabricated, whose dimension is only 0.05 λ 0 at the lower band. The simulated results agree with measured results very well.